Students' Difficulties in Understanding Quantifiers in Countable And Uncountable Nouns (A Study was Conducted at SMP Negeri 10 Kota Gorontalo) - Talibana, Srirahayu; Ibrahim, Moh Syahrun; Sambouw, Elsje Louise; Dako, Rahman Taufiqrianto; Mahmud, Muzdalifah (Jurnal Bahasa, Sastra, dan Budaya, 2024)
This research investigates the difficulties faced by students in understanding quantifiers in countable and uncountable nouns at SMP Negeri 10 Kota Gorontalo. The respondents used in this research were 15 students in class 8.1 of SMP Negeri 10 Kota Gorontalo. The aim of this research is to identify the students' difficulties and to find out the factors that cause students to experience difficulties in understanding quantifiers in countable and uncountable nouns. This research uses qualitative methods and interviews as data collection techniques. In addition, this research uses thematic analysis from Braun and Clarke (2006) as a data analysis technique. The results of this research show that class 8.1 students at SMP Negeri 10 Kota Gorontalo experience difficulties in understanding quantifiers in countable nouns, quantifiers in uncountable nouns, and quantifiers in both (countable and uncountable nouns) which is caused by a lack of basic understanding of countable and uncountable nouns,  basic understanding of quantifiers, and lack of understanding of the concept of rules for using quantifiers in countable and uncountable nouns.